Annual Incidence of Snake Bite in Rural Bangladesh - Rahman, Ridwanur (Public Library of Science, 2010)
BACKGROUND: Snake bite is a neglected public health problem in the world and one of the major causes of mortality and morbidity in many areas, particularly in the rural tropics. It also poses substantial economic burdens on the snake bite victims due to treatment related expenditure and loss of productivity. An accurate estimate of the risk of snake bite is largely unknown for most countries in the developing world, especially South-East Asia. METHODOLOGY/PRINCIPAL FINDINGS: We undertook a national epidemiological survey to determine the annual incidence density of snake bite among the rural Bangladeshi population. Information on frequency of snake bite and individuals' length of stay in selected households over the preceding twelve months was rigorously collected from the respondents through an interviewer administered questionnaire. Point estimates and confidence intervals of the incidence density of snake bite, weighted and adjusted for the multi-stage cluster sampling design, were obtained. Out of 18,857 study participants, over one year a total of 98 snake bites, including one death were reported in rural Bangladesh. The estimated incidence density of snake bite is 623.4 / 100,000 person years (95% C I 513.4–789.2 /100,000 person years). Biting occurs mostly when individuals are at work. The majority of the victims (71%) receive snake bites to their lower extremities. Eighty-six percent of the victims received some form of management within two hours of snake bite, although only three percent of the victims went directly to either a medical doctor or a hospital. CONCLUSIONS/SIGNIFICANCE: Incidence density of snake bite in rural Bangladesh is substantially higher than previously estimated. This is likely due to better ascertainment of the incidence through a population based survey. Poor access to health services increases snake bite related morbidity and mortality; therefore, effective public health actions are warranted.